PENINGKATAN KUALITAS PEMBELAJARAN DOSEN MELALUI PENUGASAN DI SEKOLAH - Hagus Muryanto; Ninik Srijani; Nurhadji Nugraha; Parji Parji; R. Bekti Kiswardianta (Jurnal Pendidikan, 2008)
The quality  of products  of a  Teacher Training  Institution  does not merely  depend  on the grade point everage they pursue,  but also on the competitive   advantage  they gain during  the learning   process to fight for position  and apply the pedagogical  priciples  in the work market  share.  The  quality of teaching  and' learning  process   in the campus  should  be then  fitted to  such  needs  of  the market   share, which  can  be  done  by sending lecturers   to  schools   as  apprentice teachers.This Peer Grant Research is aimed at: 1) developing  the quality of lecturers'  instruction, 2) developing relationship between IKIP PGRI Madiun   and  the  peer  institutions,   3) searching   and  implementing alternative     strategies    for  teaching    and  learning    effectiveness. Collaborative   teaching  between  lecturers  of IKIP PGRI Madiun  and teachers  of SMP N 11 Madiun  is designed  to: 1) observe  the existing condition  of classes,  2) discuss  for developing  alternative  strategies, 3) arrange and implement  the instructional  design, 4) conduct teaching and learning  process,  and 5) suggest  evaluation.  Class  observation, questionaire   and interview  are used to draw data from 7 subjects  in research,   i.e.:  Bahasa   Indonesia,   English,   Natural   Science,  Social Science,  Math, Civics  and Counseling.The  results   of  the  research   can  be  outlined   as  follows:   1) lecturers   develop   their  classes   by  inspecting    and  implementing directly the instruction  in real scholls'  classes, 2) identification  against weaknesses  in schools'  classes can be arranged for further evaluation, 3) the campus  develops  teacher  training  instructional   designs  based on field inventions,  4) collaborative  team invent alternative  strategies in classes, 5) lecturers experience real schools classes so as to develop their instructional design, 6) teachers are motivated to continously develop their teaching to gain optimal out-come.